Digital Tools for Masonry Design and Construction - Gentry, T. Russell (ARCC Conference Repository, 2013)
One view of conceptual design in architecture is as a negotiation between materials and forms. The process of configuring materials: organizing them, ordering them, arraying them emerges in the creative nature of design practice and the underpinnings of this process are embodied in the tools of architectural inquiry, traditionally: sketching, diagramming, modeling and drawing, and now in the digital age: another form of modeling, in design scripting, and in simulation. Two paradigms dominate digital design tools –surface modeling tools that provide few formal boundaries and no feedback on material realities – and material-aware building information modeling tools that are pre-coded with material and assembly logics. This paper focuses on the difficult middle ground, on design tools, envisioned by architects and technologists, that seek to preserve design flexibility, while embedding design reasoning and material logics. The focus is on masonry materials and systems. Masonry has come late to BIM because of its many forms, types and patterns and because its ability to adapt to complex shapes, make it difficult to instantiate incurrent BIM platforms. This paper reviews and analyzes four notable masonry buildings, and envisions the computational tools that would support the design, detailing and analysis of these buildings. It represents one component of a comprehensive project, funded by the masonry industry, to develop a software specification and workflows for integrated computational tools to support masonry design and construction.